Bilateral Isolated Congenital Microblepharon: A Rare Entity and Review of Literature - T Monikha; Sujeeth Modaboyina; Deepsekhar Das; Mandeep Singh Bajaj (Delhi Journal of Ophthalmology)
Microblepharon is an extremely rare form of congenital anomaly of the eyelids defined as vertical shortening of anterior lamellae of the eyelids. Fuch's had defined the ‘height’ of upper lid as the distance from the margin of the upper lid to the centre of the brow when the eyes are closed, and ‘length’ as the same measurement when the lid is stretched maximally. The ratio of lid length to height normally exceeds 1.5 and any value less than this is taken as microblepharon. Microblepharon is usually associated with other congenital anomalies, as described in many literatures. Isolated microblepharon is extremely rare and exhaustive literature search revealed only one such previously reported case. We report a case of bilateral isolated congenital microblepharon, and the first of its kind which required no surgical intervention.